2016
DOI: 10.1021/acsami.6b03842
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photoelectrochemical Performance from Rationally Designed Anatase/Rutile TiO2 Heterostructures

Abstract: In a photoelectrochemical (PEC) cell for water splitting, the critical issue is charge separation and transport, which is usually completed by designing semiconductor heterojunctions. TiO2 anatase-rutile mixed junctions could largely improve photocatalytic properties, but impairs PEC water splitting performance. We designed and prepared two types of TiO2 heterostructures with the anatase thin film and rutile nanowire phases organized in different sequences. The two types of heterostructures were used as PEC ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
107
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 155 publications
(113 citation statements)
references
References 42 publications
6
107
0
Order By: Relevance
“…29 This indicated that Sidoping could suppress the phase transformation from anatase to rutile, the result was in agreement with previous report.…”
Section: Electronic Structure Calculationsupporting
confidence: 92%
See 1 more Smart Citation
“…29 This indicated that Sidoping could suppress the phase transformation from anatase to rutile, the result was in agreement with previous report.…”
Section: Electronic Structure Calculationsupporting
confidence: 92%
“…The reversible hydrogen potential V RHE could be obtained according to the equation of V RHE ¼ V Ag/AgCl + 0.059pH + 0.199, 29 where V Ag/AgCl represents the applied bias, and pH value is 13.6 for the KOH electrolyte. As shown in Fig.…”
Section: à2mentioning
confidence: 99%
“…Figure S15 shows the room-temperature photoluminescence (PL) spectra, which demonstrates that the CdS/TiO 2 /Bi 2 WO 6 displays the lower intensity than CdS/Bi 2 WO 6 , indicating the appropriate thick TiO 2 layer can reduce the recombination of photo-generated electron-hole pairs, [43] which is in accordance with the separation efficiency result. The carrier density can be calculated through the following equation: [44] Typically, the slope of plot is related to the type of semiconductor and carrier concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Figure a shows the Mott–Schottky (M–S) plot of 1/ C 2 as a function of the applied potential, from which positive slopes were observed, suggesting n‐type semiconductors. [2b] Furthermore, the carrier density ( N D ) of the samples could be calculated from Figure a according to the following equationNnormalD=2normal/eεε0[]normaldUnormalFLnormal/d1/C2where e is the electron charge (1.6 × 10 −19 C), ε 0 is the permittivity of the free space (8.86 × 10 −12 F m −1 ), ε is the dielectric constant of the semiconductor (48 for anatase TiO 2 ), and C is the capacitance. In our case, the N D value of rGO/ATRCs reaches as high as 4.3 × 10 19 cm −3 , which is much higher than that of common rGO/TNPs (7.15 × 10 18 cm −3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the higher N D of rGO/ATRCs signifies lesser trap sites than that in rGO/TNPs for favorable electron transfer, thus leading to enhanced photovoltaic performance. [2a]…”
Section: Resultsmentioning
confidence: 99%